Pelestarian Aspek Kesemestaan Dan Kesetempatan Dalam Arsitektur Bangsal Sitihinggil Di Kraton Yogyakarta - Suryono, Alwin (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2016)
The Sitihinggil Kraton Yogyakarta building, completed in 1926, has a EuropeanJavanese architecture style. It is originally a coronation place of the Mataram Sultans and the first Indonesia President. In the present time, it is used for royal official ceremonies and tourist attractions. The purpose of this study is to reveal the universallocal aspects of Sitihinggil architecture and describe its conservation concept. The method used is descriptive-explanatory, with the approach of Javanese CultureArchitecture-Conservation. The universal aspect is based on the Javanese culture philosophy â€unitary natural-social-spiritual interactionâ€, whereas the local aspects are â€œphilosophy of toleranceâ€ and architecture style. Natural relation associates with symmetrical space layout towards the philosophical axis and the adaptive building (to the environment). The social relation associates with the dialogue between the Sultan (inside the building) with the people (sitting in the North Square). The spiritual relation associates with the Sultanâ€™s meditation ritual in this building while looking at the White Postâ€™s direction. â€œToleranceâ€ philosophy could be seen through the architectural styles. Conservation concept: Preservation of space layout (opennessposition of the building); Restoration of the North Square (thickened the surrounding grass and trees); Preservation-routine maintenance of building (Roofs, ceilings, beams, gutters, windows, pillars, ornaments)Keywords: universal, local, culture, preservation.